Uptake and Translocation of some heavy metals (Nickel, Chromium, Cobalt, Cadmium, Lead) by Rice crop in Paddy soils (International Journal of Food and Nutritional Sciences, 2022)
The goal of the current study is to assess the translocation of five heavy metals—nickel, chromium, cobalt, cadmium, and lead—from soil to rice and wheat, two significant food crops in India. The research area's soil was sampled between April and November 2021. The presence of heavy metals in the soil was found with the help of a flame atomic absorption spectrophotometer. The result showed that heavy metals concentration in plant root (mg kg-1) was as follows: Ni (0.496 ± 0.045), Co (0.301 ± 0.052),Pb (0.244 ± 0.052), Cr (0.193 ± 0.00), Cd (0.070 ± 0.030), and in plant stem it was: Ni (0.294 ± 0.040), Pb (0.227 ± 0.035), Cr (0.052 ± 0.00), Co (0.106 ± 0.014), Cd (0.030 ± 0.00), and in plant grains it was Pb(0.051 ± 0.013), Ni (0.046 ± 0.012), Co (0.057 ± 0.009), Cd (0.013 ± 0.00), and Cr was zero. The average concentration of all measured heavy metals in crop parts was below permissible levels as per Indian standards.